1995
DOI: 10.1007/bf01781200
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two commercial amplification assays for detection ofMycobacterium tuberculosis complex in respiratory specimens

Abstract: To evaluate the usefulness of two standardized commercially available amplification assays for the detection of Mycobacterium tuberculosis: Amplicor test (Roche) and MTD-Amplified direct test (Gen-Probe) a total of 281 respiratory specimens from 198 patients with symptoms of pulmonary diseases were examined and compared with conventional methods. Fifty-seven specimens were positive and 218 negative by both amplification assays. Three specimens were reactive by Amplicor only, and three by MTD only. In compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…[12][13][14][15] In these studies between 10.5% and 34.1% of the tested specimens were positive for M tuberculosis. The specificity of the LCx Mycobacterium tuberculosis assay has been reported by its manufacturer 9 to be 99.3% for 1971 respiratory specimens, of which 8% were culture positive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15] In these studies between 10.5% and 34.1% of the tested specimens were positive for M tuberculosis. The specificity of the LCx Mycobacterium tuberculosis assay has been reported by its manufacturer 9 to be 99.3% for 1971 respiratory specimens, of which 8% were culture positive.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the sensitivities for both the Amplicor Mycobacterium tuberculosis test and the Amplified Mycobacterium tuberculosis direct test to be between 80% and 99% when used to test microscopy positive respiratory specimens. [12][13][14][15] The LCx Mycobacterium tuberculosis assay is claimed by its manufacturers to have a sensitivity of 93.7% 9 with similar specimens, and other reports have shown sensitivities between 90.8% and 90.2%. 8 16 In our present study, the results for the Amplicor Mycobacterium tuberculosis test for specimens that were both microscopy positive and culture positive were similar to those reported by others.…”
Section: Discussionmentioning
confidence: 99%
“…A limited number of comparisons of DATs developed for the commercial market have been reported, [5][6][7] but their application in the routine laboratory setting has not been adequately addressed. The first-generation Gen-Probe Amplified Mycobacterium Tuberculosis Direct (MTD) test (Gen-Probe, San Diego, Calif) and the Roche Molecular AMPLICOR MTB system (Roche Molecular Systems, Branchburg, NJ) are approved by the US Food and Drug Administration for the detection of MTB complex (M tuberculosis, Mycobacterium bovis, including BCG strain, Mycobacterium microti, and Mycobacterium africanum) in acid-fast smear-positive respiratory specimens collected from untreated patients.…”
Section: -2 and Laboratoriesmentioning
confidence: 99%
“…The Amplified Mycobacterium Tuberculosis Direct Test (AMTDT 2; Gen Probe, USA) and the Cobas Amplicor Mycobacterium Tuberculosis Test (Roche, Switzerland) are highly standardized and automated second-generation assays for detection of Mycobacterium tuberculosis, with reported sensitivities of 86-100% and 83-98%, and specificities of 94-100% and 92-100%, respectively [1,[3][4][5]. Following studies in which controversial results were obtained with various amplification assays, the role of these assays in monitoring treatment response remains undefined [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Amplification assays have been shown to enhance the rapid diagnosis of pulmonary tuberculosis [1][2][3]. The Amplified Mycobacterium Tuberculosis Direct Test (AMTDT 2; Gen Probe, USA) and the Cobas Amplicor Mycobacterium Tuberculosis Test (Roche, Switzerland) are highly standardized and automated second-generation assays for detection of Mycobacterium tuberculosis, with reported sensitivities of 86-100% and 83-98%, and specificities of 94-100% and 92-100%, respectively [1,[3][4][5].…”
Section: Introductionmentioning
confidence: 99%